AKIBAT HUKUM SAHAM YANG DIKELUARKAN PERSEORAN TANPA TERLEBIH DAHULU DITAWARKAN KEPADA PEMEGANG SAHAM - Ghansam Anand (Yuridika, 2012)
The principle of freedom of contract was absolutely owned by anyone in making engagement therefore there should be no intervention of the king or state. Exposure theory in this paper aims that every person to own the freedom to enter into an engagement. This freedom also lies not only in his attitude to enter into an engagement but also about the object that is set by the engagement that they make. State, in this case is the government, should not intervene in the engagement that they make.Keyword: Agreement, Company, Stock.